STRATEGIES TO IMPROVE OPERATIONAL READINESS OF THE INDONESIAN NAVY'S ANTI-SUBMARINE HELICOPTERS IN ANTI-SUBMARINE WARFARE USING THE TECHNOMETRIC METHOD - Muksin Muksin; Udisubakti Cipto Mulyono; Sutrisno Sutrisno (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT Naval operational readiness is readiness in building operational readiness for naval defense through budget fulfillment, utilization of existing resources, procurement and naval modernization by paying attention to Life Cycle Cost, and interoperability while still paying attention to paradigm shifts in naval capability.Combat readiness is the condition of the Indonesian Navy's defense equipment and its constituent units, resources and personnel, weapon systems and other military technology equipment in a condition that is ready to carry out military operations in an unspecified time, or function consistent with the purpose for which the defense equipment is organized or designed. , the management of resources and training personnel in preparation for combat in the face of the threat of modern warfare in a state of constant combat readiness. At this time, training in Anti-Submarine Warfare conducted by Indonesian Navy’s Helicopter is still limited to carrying out flight procedures, communication procedures with the KRI and the command line, because Helicopters have sensors, weapons and command that need to be upgraded and The personnel also have underwater warfare capabilities that need to be upgraded, so there needs to be an increase in the capability of the helicopter and human resources. Technometry will be used to calculate the Heli's current readiness level. Keywords: Operational readiness, Technometic.